2011
DOI: 10.1080/03079457.2011.588940
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic microorganisms carried by migratory birds passing through the territory of the island of Ustica, Sicily (Italy)

Abstract: Several studies have shown that migratory birds play an important role in the ecology, circulation and dissemination of pathogenic organisms. In October 2006, a health status evaluation was performed on a large population of migratory birds passing through the territory of Ustica (Italy), an island located on the migration route of many species of birds to Africa, and various laboratory tests were conducted. In total, 218 faecal swabs and the internal organs of 21 subjects found dead in nets were collected for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
2
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 34 publications
(31 reference statements)
4
36
2
7
Order By: Relevance
“…Interestingly, mycoses are sporadic in wild birds that are not fed by humans (23), while carrier-state, especially in water fowl, is reported more frequently than in other vertebrates (8,25). Fungi can be transmitted by birds in a passive manner (on the body surface or in feathering), by biological vectors (ectoparasites), or in the internal organs, mainly in the respiratory and digestive tracts, as evidenced by the close correspondence of the obtained results with the observations of other authors (17,18,25).…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…Interestingly, mycoses are sporadic in wild birds that are not fed by humans (23), while carrier-state, especially in water fowl, is reported more frequently than in other vertebrates (8,25). Fungi can be transmitted by birds in a passive manner (on the body surface or in feathering), by biological vectors (ectoparasites), or in the internal organs, mainly in the respiratory and digestive tracts, as evidenced by the close correspondence of the obtained results with the observations of other authors (17,18,25).…”
Section: Introductionsupporting
confidence: 71%
“…However, C. neoformans is a fungus that is thought to be the most dangerous to humans, especially to children. It is believed to be the most common commensal of birds (13,17,18,22) in which it asymptomatically colonises the skin, subcutaneous tissue, and lungs. This fungus is common in the lithosphere and easily develops in the Polish climate (particularly in autumn) on the faeces of different avian species and in faeces-contaminated soil (13).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is commonly thought that early detection of avian influenza is essential for economic security in the poultry industry and maintenance of public health [32]. Previously, avian influenza has been monitored in wild birds, including those in Italy and those crossing the Europe/North America land bridge [11,[33][34][35][36][37]. We investigated for the first time the influenza strains currently affecting the migratory birds landing in the island of Sardinia, a land bridge between Europe and Africa.…”
Section: Introductionmentioning
confidence: 99%
“…LPAI viruses infect the intestinal tract of avian species typically through the fecal-oral route, whereas the HPAI viruses with mutated polybasic amino acids in the HA cleavage site can infect a range of tissues and organs outside of the gut [8,9]. Studies have implicated migratory birds in the spread of pathogenic organisms including the influenza virus, although controversy exists surrounding the ability of migratory birds to disseminate HPAI strains and the clinical disease caused by infection [7,8,[10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that migratory wild birds play an important role in the ecology, circulation and dissemination of enteric human pathogens such as Campylobacter, Salmonella, toxin-producing Escherichia coli and antimicrobial resistant organisms (Reed et al 2003;Abulreesh et al 2007;Foti et al 2011;Magda et al 2013).…”
Section: Introductionmentioning
confidence: 99%